SERS study of a tetrapeptide based on histidine and glycine residues, adsorbed on copper/silver colloidal nanoparticles. (8th May 2014) - Gellini, Cristina; Sabatino, Giuseppina; Papini, Anna Maria; Muniz‐Miranda, Maurizio
<x xml:space="preserve">Abstract</x> Surface‐enhanced Raman scattering has been employed to characterize the adsorption of an oligopeptide containing histidine residues on colloidal nanoparticles of metals as Ag and Cu obtained by laser ablation. The title molecule consists of two histidine and glycine residues alternating along the chain and terminating with an acetyl on one side and an amide group on the other. Histidine residues are found to act as docking sites of the molecule to the surface of the metal nanoparticles. Semiempirical parameterized model number 3 (PM3) calculations performed on molecule/metal model complexes suggest possible different adsorption geometries depending on the metallic substrate. This investigation could provide useful information to address the interaction of protein systems with metal ions, which is often related to fundamental biological process in living systems and can play an important role in different neuropathological diseases. Copyright © 2014 John Wiley & Sons, Ltd.